ANALISIS KONJUNGTOR DALAM KOLOM EDITORIAL SURAT KABAR LAMPUNG POST - Dewi Ratnaningsih; Rahmat Prayogi; Rian Andri Prasetya (FKIP Universitas Lampung, 2021)
The purpose of this study was to describe conjunction within the rubric of